Modernism, Inflation and the Gold Standard in T.S. Eliot and Ezra Pound. Issue 3 (August 2021) - Hawkes, David
Abstract : The great inflation of the 1920s had a dramatic effect on Anglophone literary modernism. Ezra Pound, T.S. Eliot and Ernest Hemingway all recognized that financial signs had come unmoored from any objective reference, and their work explores the literary implications of representation's newly autonomous, performative power. Pound blamed the economic and cultural crisis on 'usury.' Following Aristotle, he conceived of usury as the unnatural reproduction of autonomous representation, and thus as the antithesis of natural sexual and semiotic fertility. He particularly deplored the historical role played by Samuel Loyd, the Victorian head of Lloyds Bank, who had cunningly manipulated the gold standard in order to give control of the economy to 'usurers.' In his financial journalism for Lloyds Bank Monthly, Eliot used the gold standard as an economic logos in order to facilitate usury. Pound saw that Eliot's theory of the 'objective correlative' was incompatible with the referential model of representation assumed by the gold standard.